Informing phenomenological structural bone remodelling with a mechanistic poroelastic model - Villette,CC; Phillips,ATM (Biomechanics and Modeling in Mechanobiology, 2015)
t Studies suggest that fluid motion in the extracellularspace may be involved in the cellular mechanosensitivityat play in the bone tissue adaptation process. Previously,the authors developed a mesoscale predictive structuralmodel of the femur using truss elements to represent trabecularbone, relying on a phenomenological strain-basedbone adaptation algorithm. In order to introduce a responseto bending and shear, the authors considered the use of beamelements, requiring a new formulation of the bone adaptationdrivers. The primary goal of the study presented herewas to isolate phenomenological drivers based on the resultsof a mechanistic approach to be used with a beam elementrepresentation of trabecular bone in mesoscale structuralmodelling. A single-beam model and a microscale poroelasticmodel of a single trabecula were developed. A mechanisticiterative adaptation algorithm was implemented based onfluid motion velocity through the bone matrix pores to predictthe remodelled geometries of the poroelastic trabeculaunder 42 different loading scenarios. Regression analyseswere used to correlate the changes in poroelastic trabeculathickness and orientation to the initial strain outputsof the beam model. Linear (R2 > 0.998) and third-orderpolynomial (R2 > 0.98) relationships were found betweenchange in cross section and axial strain at the central axis,and between beam reorientation and ratio of bending strainto axial strain, respectively. Implementing these relationships into the phenomenological predictive algorithm for themesoscale structural femur has the potential to produce amodel combining biofidelic structure and mechanical behaviourwith computational efficiency.